Lower body negative pressure to safely reduce intracranial pressure. (20th November 2018) - Petersen, Lonnie G.; Lawley, Justin S.; Lilja‐Cyron, Alexander; Petersen, Johan C. G.; Howden, Erin J.; Sarma, Satyam; Cornwell, William K.; Zhang, Rong; Whitworth, Louis A.; Williams, Michael A.; Juhler, Marianne; Levine, Benjamin D.
Abstract : Key points: During long‐term missions, some astronauts experience structural and functional changes of the eyes and brain which resemble signs/symptoms experienced by patients with intracranial hypertension. Weightlessness prevents the normal cerebral volume and pressure 'unloading' associated with upright postures on Earth, which may be part of the cerebral and ocular pathophysiology. By placing the lower body in a negative pressure device (LBNP) that pulls fluid away from cranial compartments, we simulated effects of gravity and significantly lowered pressure within the brain parenchyma and ventricle compartments. Application of incremental LBNP demonstrated a non‐linear dose–response curve, suggesting 20 mmHg LBNP as the optimal level for reducing pressure in the brain without impairing cerebral perfusion pressure. This non‐invasive method of reducing pressure in the brain holds potential as a countermeasure in space as well as having treatment potential for patients on Earth with traumatic brain injury or other pathology leading to intracranial hypertension. Abstract: Patients with elevated intracranial pressure (ICP) exhibit neuro‐ocular symptoms including headache, papilloedema and loss of vision. Some of these symptoms are also present in astronauts during and after prolonged space‐flight where lack of gravitational stress prevents daily lowering of ICP associated with upright posture. Lower body negative pressure (LBNP) simulates the effects of gravity by displacing fluid caudally and we hypothesized that LBNP would lower ICP without compromising cerebral perfusion. Ten cerebrally intact volunteers were included: six ambulatory neurosurgical patients with parenchymal ICP‐sensors and four former cancer patients with Ommaya‐reservoirs to the frontal horn of a lateral ventricle. We applied LBNP while recording ICP and blood pressure while supine, and during simulated intracranial hypertension by 15° head‐down tilt. LBNP from 0 to 50 mmHg at increments of 10 mmHg lowered ICP in a non‐linear dose‐dependent fashion; when supine ( n = 10), ICP was decreased from 15 ± 2 mmHg to 14 ± 4, 12 ± 5, 11 ± 4, 10 ± 3 and 9 ± 4 mmHg, respectively ( P < 0.0001). Cerebral perfusion pressure (CPP), calculated as mean arterial blood pressure at midbrain level minus ICP, was unchanged (from 70 ± 12 mmHg to 67 ± 9, 69 ± 10, 70 ± 12, 72 ± 13 and 74 ± 15 mmHg; P = 0.02). A 15° head‐down tilt ( n = 6) increased ICP to 26 ± 4 mmHg, while application of LBNP lowered ICP (to 21 ± 4, 20 ± 4, 18 ± 4, 17 ± 4 and 17 ± 4 mmHg; P < 0.0001) and increased CPP ( P < 0.01). An LBNP of 20 mmHg may be the optimal level to lower ICP without impairing CPP to counteract spaceflight‐associated neuro‐ocular syndrome in astronauts. Furthermore, LBNP holds clinical potential as a safe, non‐invasive method for lowering ICP and improving CPP for patients with pathologically elevated ICP on Earth. Key points: During long‐term missions, some astronauts experience structural and functional changes of the eyes and brain which resemble signs/symptoms experienced by patients with intracranial hypertension. Weightlessness prevents the normal cerebral volume and pressure 'unloading' associated with upright postures on Earth, which may be part of the cerebral and ocular pathophysiology. By placing the lower body in a negative pressure device (LBNP) that pulls fluid away from cranial compartments, we simulated effects of gravity and significantly lowered pressure within the brain parenchyma and ventricle compartments. Application of incremental LBNP demonstrated a non‐linear dose–response curve, suggesting 20 mmHg LBNP as the optimal level for reducing pressure in the brain without impairing cerebral perfusion pressure. This non‐invasive method of reducing pressure in the brain holds potential as a countermeasure in space as well as having treatment potential for patients on Earth with traumatic brain injury or other pathology leading to intracranial hypertension.